1999
DOI: 10.1165/ajrcmb.20.4.3407
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Interferon- γ –Producing Lung Lymphocytes in Mouse Silicosis

Abstract: Silicosis is characterized by mononuclear cell inflammation with macrophage activation, accumulation of lymphocytes, and fibrosis. Interferon-gamma (IFN-gamma) is a lymphocyte cytokine with broad effects, particularly macrophage activation. Mice exposed to an aerosol of cristobalite silica (70 mg/m3, 12 d, 5 h/d) developed diffuse pulmonary pathologic changes with macrophage, lymphocyte, and neutrophil recruitment, and increased lung collagen. IFN-gamma messenger RNA (mRNA) was more abundant by semiquantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…Similar to this hypothesized role for IFN-␥ in bleomycin-induced pulmonary fibrosis, the fibrotic response to intratracheal silica (another lung injury-inducing agent) exposure in rodents has also been shown to be dependent on IFN-␥, IL-12, and TNF-␣ (29).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Similar to this hypothesized role for IFN-␥ in bleomycin-induced pulmonary fibrosis, the fibrotic response to intratracheal silica (another lung injury-inducing agent) exposure in rodents has also been shown to be dependent on IFN-␥, IL-12, and TNF-␣ (29).…”
Section: Discussionmentioning
confidence: 73%
“…Our findings that IFN-␥ may play a profibrotic role under certain conditions in experimental bleomycin-induced pulmonary toxicity have possible implications for human disease. First, these observations suggest that IFN-␥ could play a profibrotic role in the lung fibrosis that occurs in diseases associated with enhanced chronic production of IFN-␥ such as sarcoidosis, chronic beryllium disease, silicosis, and hypersensitivity pneumonitis (29,(39)(40)(41)(42). In these diseases, chronic lung injury secondary to the proinflammatory effects of IFN-␥ could theoretically result in progressive lung fibrosis (43).…”
Section: Discussionmentioning
confidence: 99%
“…Both Th1 and Th2 polarization during experimental silicosis have already been reported. Although IL-4 expression was unchanged or decreased, Davis and colleagues (12) showed an increased IFN-␥ response in the lung of mice with silicosis, suggesting a Th1-like lymphocyte-mediated immune response. Opposite results showed that in wild-type animals, silica-induced fibrosis was correlated with markers of a Th2-like response such as upregulation of IL-4 levels in lung tissue and an increased immunoglobulin IgG1/IgG2a ratio in BAL (24).…”
Section: Discussionmentioning
confidence: 98%
“…Both Th1 (8,13,14,17,18,22,51) and Th2 responses (1,4,10,22) have been found to be associated with the development of silicosis. Thus, in our study, we examined the potential role of type 2 immune polarization by investigating the functions of IL-4 and IL-13 in the fibrotic process in response to silica particles in C57BL/6 wild-type, IL-4 Ϫ/Ϫ , and IL-4R␣ Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
“…IL-4 expression was also shown to be increased in the lungs of silica-treated rats (10). By contrast, overproduction of IFN-␥ by lung and thoracic lymph node T lymphocytes was reported in mice and rats developing silicosis (13,14,17,18,22). A predominance of Th1 immune response in silicosis was also evidenced by enhanced levels of serum IgG 2a (51) but reduced serum IgG 1 concentrations in silica-treated mice (8).…”
mentioning
confidence: 99%